2019
DOI: 10.1177/2167702619855035
|View full text |Cite
|
Sign up to set email alerts
|

Riskier Tests of the Validity of the Bifactor Model of Psychopathology

Abstract: We advanced several “riskier tests” of the validity of bifactor models of psychopathology, which included that the general and specific psychopathology factors should be reliable and well represented by their respective indicators and that including a general factor should improve on the correlated factor model’s external validity. We compared bifactor and correlated factors models of psychopathology using data from a community sample of youth ( N = 2,498) whose parents provided ratings on psychopathology and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

18
256
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(275 citation statements)
references
References 84 publications
18
256
1
Order By: Relevance
“…In contrast, because all factors are orthogonal in bifactor models, one can simultaneously regress measured criterion variables on the general and specific factors to determine if each of these factors independently accounts for unique variance in that variable. Such advantages of bifactor models for discovering the correlates of psychopathology at each level of the hierarchy are not in dispute (Bornovalova et al, 2020;Watts, Poore, & Waldman, 2019). What is in dispute, however, is whether the psychometric properties of all factors in bifactor models are sufficient to realize its logical advantages (Conway, Mansolf, & Reise, 2019;Watts et al, 2019).…”
Section: General Scientific Summarymentioning
confidence: 99%
“…In contrast, because all factors are orthogonal in bifactor models, one can simultaneously regress measured criterion variables on the general and specific factors to determine if each of these factors independently accounts for unique variance in that variable. Such advantages of bifactor models for discovering the correlates of psychopathology at each level of the hierarchy are not in dispute (Bornovalova et al, 2020;Watts, Poore, & Waldman, 2019). What is in dispute, however, is whether the psychometric properties of all factors in bifactor models are sufficient to realize its logical advantages (Conway, Mansolf, & Reise, 2019;Watts et al, 2019).…”
Section: General Scientific Summarymentioning
confidence: 99%
“…A prominent example in abnormal psychology is the general factor of psychopathology (p factor; Caspi and Moffitt 2018;Lahey et al 2012). After reviewing the research on the p factor of psychopathology over the last eight years, Watts et al (2019) concluded that "the precise nature of the p factor is not yet understood" (p. 1285). It is only recently that systematic analyses of applications of the bifactor model revealed that many applications are affected by serious problems (e.g., negative variances of specific factors, vanishing specific factors, irregular loadings patterns; see, for example, Eid et al 2017).…”
mentioning
confidence: 99%
“…Moreover, the results of these applications are typically not in line with the theoretical expectations. For example, Watts et al (2019) convincingly stated that from a theoretical point of view all observed variables of a bifactor model should have relatively equal loadings on the common general factor and each facet should be represented by a specific factor. This structure, however, is often not supported (Eid et al 2017;Watts et al 2019).…”
mentioning
confidence: 99%
See 2 more Smart Citations